Long Term Follow up of Patients With Primary Obstetric Antiphospholipid Syndrome - Niznik, Stanley; Rapoport, Micha J.; Avnery, Orly; Lubetsky, Aharon; Shavit, Ronen; Ellis, Martin H.; Agmon-Levin, Nancy (Frontiers in Pharmacology, 2022)
Introduction – Primary obstetric antiphospholipid syndrome (OAPS) is defined by specific morbidities and/or losses of pregnancy in the presence of persistent antiphospholipid antibodies (aPL). This variant of APS is usually treated during pregnancy and the post-partum period. Data on occurrence of thrombotic event during long term follow-up of OAPS patients is limited. Methods – A multi-centre retrospectively cohort of female patients with primary APS (pAPS) was assembled during 2004-2019. Patients were grouped according to disease presentation as pure OAPS or thrombotic APS (tAPS) for those presenting with thrombosis. Clinical and serological data were compared between groups. Results – Of 219 pAPS female patients 67(30.6%) were diagnosed with OAPS and 152(69.4%) with tAPS. During > 10 years of follow-up 24/67(35.8%) OAPS and 71/152(50%) tAPS suffered a new thrombotic event (p=0.06), while obstetric morbidity was more likely in the OAPS group (31.3% vs 10.5%, p<0.001) respectively. Among patients with OAPS at presentation heart valve disease and the presence of ANA were related to thrombosis following diagnosis (25% vs 4.7%, p=0.02; and 45.8% vs 20.8%, p=0.04 respectively). Conclusion – Thrombotic event following diagnosis were common among female patients with pAPS regardless of disease presentation. Heart valve disease and ANA positivity may be risk factors for thrombosis during follow-up of patients presenting with pure OAPS.